Control of Transition Time by the Likely Future as Signalled from the Past in Children with ASD - Wood, Aleksandra; Simon, Carsta (The Psychological record, 2023)
The signaling perspective offers an alternative to the Skinnerian view of understanding behavior. The signaling effects of reinforcers have predominantly been explored in the laboratory with nonhuman subjects. To test the implications of this view for applied behavior analysis, we contrasted the effect of discriminative stimulus versus reinforcer control in children with autism spectrum disorder (ASD). We aimed to determine whether the duration of their transitions from one reinforcer context to another is controlled by their most recent past or the likely future based on more extended past experience. Reinforcer context (rich, moderate, or lean) was signaled in the first condition. We observed that transition times to the leaner reinforcer were longer than those to the richer. The reinforcer context was unsignaled in the second condition. The differences between transition times disappeared in the second condition. The difference in durations of transitions to signaled and unsignaled reinforcer densities suggests that behavior is primarily controlled by signals of likely future reinforcers as extrapolated from extended past experience rather than strengthened by the most recent event.